[PLDT ; Cry rape ; Flying high [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Deals with the announcement of PLDT about their policy of opening interconnection even with its competitors; women's group questining the rape law hoping that the lawmakers will amend it to prevent injustices done to women who are victims of heinous crimes against chastity; and the story on sky diving as exciting sport in the Philippines.